MENINGKATKAN KEMAMPUAN PENJUMLAHAN MELALUI MEDIA BALOK BERGAMBAR BAGI ANAK TUNAGRAHITA RINGAN (Single Subject Research di Kelas D4C SLB C Payakumbuh) - Yuri - Febrianti (Jurnal Penelitian Pendidikan Khusus, 2013)
This research background by mild mental retardation children problems (x) the difficulty in solving sums. Based on the observations made, it is known that children are familiar with the concept of numbers, sign (sum) and be able to count, but the children have difficulty in doing the sums though only to 10 only, from the condition indicated that children may not be able to complete the sums. Child's ability in solving addition problems is low, children are very slow to settle the sum. Researchers want the ability to increase that sum by using the beam image. The hypothesis in this study, the beam pictorial media can enhance the ability of the sum of the child mild mental retardation. This study used experimental approach in the form of Single Subject Research (SSR). As the subject of this study is the son of mental retardation (x) was 13 years old. Assessment of this research is shaped by counting the percentage of correct answers is done by children divided by the number of questions X 100%. Data acquired and processed in the form of graphs, so that the results can be drawn between the two conditions. From the research shows that the ability to sum ​​up the results of 10 for child mental retardation X increases. Initially the children are able to solve problems with the acquisition sum percentage of correct answers between 30% - 50%, after a given intervention by using the beam pictorial percentage of correct answers increased to 40% - 80%. Thus the hypothesis put forward previously acceptable. This means that media can enhance the ability of the beam pictorial summation of child mental retardation.